2001
DOI: 10.1023/a:1011205221972
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Next to in vitro-cultured autogeneic keratinocytes for the restoration of epidermis, a suitable dermal matrix is a mandatory component of an artificial skin substitute for the permanent covering of full thickness skin defects. In our model a xenogeneic membrane, consisting of processed native collagen and elastin of porcine origin is meant to serve as a template for the formation of a neo-dermis. In order to improve the resistance of this matrix against enzymatical degradation, we cross-linked it by using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…In this study, EDC and NHS were added to increase the rate and amount of crosslinking between –COOH groups present in the decellularized goat-lung tissue (collagen-based biomaterial) and –NH 2 groups present in the CS/nHAp composite, thereby increasing the compressive stiffness of the scaffold [3032]. …”
Section: Resultsmentioning
confidence: 99%
“…In this study, EDC and NHS were added to increase the rate and amount of crosslinking between –COOH groups present in the decellularized goat-lung tissue (collagen-based biomaterial) and –NH 2 groups present in the CS/nHAp composite, thereby increasing the compressive stiffness of the scaffold [3032]. …”
Section: Resultsmentioning
confidence: 99%
“…Previous research by Hafemann et al showed no significant difference in cell growth or spreading after crosslinking [12]. They studied the biocompatibility of non-/crosslinked collagen–elastin films using fibroblasts and keratinocytes.…”
Section: Discussionmentioning
confidence: 98%
“…No difference was observed between the two groups. Scale bar = 50 μm affecting its biocompatibility, although their cross-linking effect is relatively less potent for collagen strength comparing with the conventional reagent glutaraldehyde that is cytotoxic (Hafemann et al 2001;Park et al 2002). It might be reasonable to speculate that the combination of collagen compression, mechanical loading, new collagen cross-linking agents and other potential techniques could generate collagen gel based scaffolds for skin engineering with stronger mechanical strength and less contraction.…”
Section: Discussionmentioning
confidence: 99%